1984
DOI: 10.1002/hep.1840040209
|View full text |Cite
|
Sign up to set email alerts
|

An Antibody Which Precipitates Dane Particles in Acute Hepatitis Type B: Relation to Receptor Sites Which Bind Polymerized Human Serum Albumin on Virus Particles

Abstract: An antibody, which is distinct from the HBsAg- reacts with antigenic sites on Dane particles- HBcAg and HBeAg, was studied by radioimmunoprecipitation of radioactive intact hepatitis B virions in sera obtained early in the course of acute hepatitis type B. The antibody, previously termed anti-Dane particle (anti-DP) antibody, was reactive with Dane particles and HBsAg particles obtained from HBeAg-positive sera but not with HBsAg particles from anti-HBe containing sera. The expression on virus particles of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…On the other hand, antibodies against the pHSA receptor which have been shown in serum during acute hepatitis B may have an important role for viral clearance (Alberti et al, 1984;Pontisso et al, 1983b). As a result, it would be useful to use HBsAg particles carrying the pHSA receptor in vaccination programs (Michel et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, antibodies against the pHSA receptor which have been shown in serum during acute hepatitis B may have an important role for viral clearance (Alberti et al, 1984;Pontisso et al, 1983b). As a result, it would be useful to use HBsAg particles carrying the pHSA receptor in vaccination programs (Michel et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Also, these domains stimulate cellular immune responses and, importantly in the context of this study, can help bypass genetic nonresponsiveness to the S antigen. [14][15][16][17][18][19][20][21] This novel vaccine has been developed to produce a superior immunologic response to that of currently approved vaccines. Animal studies have indicated that it was well tolerated, 6,7 and a viral challenge study in chimpanzees has shown protective efficacy.…”
Section: ) Than a Further Attempt With A Current Vaccine (Engerix-mentioning
confidence: 99%
“…The product encoded by the pre-S region has attracted increasing attention, owing to its strong immunogenicity and association with the species-specific receptor for polymerized human and chimpanzee albumins Machida et al, 1984). Antibodies against this product may have clinical implications, because they could be responsible for the clearance of HBV from the circulation (Alberti et al, 1984). Furthermore, the pre-S(2) sequence is highly immunogenic in mice (Coursaget et al, 1985;Milich et al, 1985); it may add protective efficacy to a hepatitis B vaccine involving primarily the product of the S gene.…”
Section: Ll Ill L Iiil L L Ll L Llllelliimentioning
confidence: 99%